2008
DOI: 10.1007/s10535-008-0122-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting plant regeneration from immature inflorescence of two winter wheat cultivars

Abstract: Inflorescence explants of two winter wheat cultivars, Triticum durum cv. Kızıltan-91 and T. aestivum cv. Bezostaja-01, were used to evaluate the effects of vernalization period of donor plants, callus age and medium composition on regeneration capacity. Donor plants were grown for 7 d and they were exposed to 4 ºC for 1, 2, 3, 4, and 5 weeks. The maximum inflorescence formation was observed as 79 % at 4 weeks and 73 % at 5 weeks of vernalization period for Kızıltan-91 and Bezostaja-01, respectively. Among 6 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In Vitro PGR-induced floral reversion has been shown in a variety of dicots and monocots. In monocots, it is widely used in many commercially important crops such as grasses, palms, bananas, and grains [62,98,[100][101][102]. In dicots, floral reversion has been employed less frequently; however, it has been shown in the Brassicaceae family and has been employed in conservation efforts of recalcitrant dicots [96,97,103,104].…”
Section: Floral Reversion: An Alternate Micropropagation Approachmentioning
confidence: 99%
“…In Vitro PGR-induced floral reversion has been shown in a variety of dicots and monocots. In monocots, it is widely used in many commercially important crops such as grasses, palms, bananas, and grains [62,98,[100][101][102]. In dicots, floral reversion has been employed less frequently; however, it has been shown in the Brassicaceae family and has been employed in conservation efforts of recalcitrant dicots [96,97,103,104].…”
Section: Floral Reversion: An Alternate Micropropagation Approachmentioning
confidence: 99%
“…A good and efficient callus induction system in wheat highly depends on sterilization process, type of explants, genotypes, media composition and its pH, growth hormones, inducers and incubation conditions (Parmar et al 2012;Mamrutha et al 2014). Different explants have been tested as starting material for wheat callus cultures, such as immature embryos (Hakam et al 2015), leaf segment (Yu et al 2012), anthers (Redha and Suleman 2011), immature inflorescence (Kavas et al 2008), microspores (Shariatpanahi et al 2006) and mature embryos (Parmar et al 2012) which showed the variable response for callus induction and regeneration. Immature embryos have been found most suitable explant source due to its high callus induction and regeneration capabilities (Redway et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The difference may also be related to the medium used and the development stage of the inflorescences. Medium composition, callus age and vernalization period of donor plants were the main factors reported, which had great effects on inflorescences regeneration capacity (Kavas et al, 2008;Maddock et al, 1983;Pellegrineschi et al, 2003). Our preliminary studies indicate that the inflorescences which have yellowish transparent color with the length less than 2 mm cannot be induced into callus at all, and those with the sizes from 3 to 5 mm responded to induction medium, but not all of them can develop into callus, whereas those with the sizes from 5 to 8 mm can be initiated into callus easily.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the callus induction and regeneration system is the major one used in wheat transformation, and tissue culture capacities of different explants had great effects on transformation efficiency (Pellegrineshi et al, 2002). To date, various explants such as immature embryos (Barro et al, 1999;Fennell et al, 1996;Wu et al, 2009), inflorescences (Caswell et al, 2000;Kavas et al, 2008;Maddock et al,1983), isolated anthers (Brisbe et al, 2000;Soriano et al, 2008), isolated microspores (Mejza et al, 1993;Liu et al, 2004), mature embryos Patnaik et al, 2006;Özgen et al, 1998, and shoot tips (Haliloglu et al, 2006;Viertel et al, 1996), leaf base (Wang et al, 2004) were successfully used for tissue culture, and immature embryos, 14 days after pollination with the size about 1.0 mm, were the most common explants used for transformation.…”
Section: Introductionmentioning
confidence: 99%